Creative Economy Development Strategy in the Digital Age According to Islamic Economic Principles: Literature Review and Theoretical Analysis - Jahra, Pati Matu; Syarqawie, Fithriana; Badrian, Badrian (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study explores strategies for developing the creative economy in the digital era based on Islamic economic principles, such as justice, transparency, and prohibitions against usury (riba) and gambling (maysir). Using a literature review and theoretical analysis, this research examines the alignment between creative economy practices and Shariah values. Data sources include relevant journals, books, and publications, with content analysis used to identify strategies aligned with a Shariah-compliant creative economy. The findings indicate that applying Islamic economic principles can be achieved through value-based innovation, profit-sharing business models, and digital technology for transparency. Practical implications include recommendations for businesses to adopt Shariah principles in their strategies and for policymakers to support regulations that facilitate a Shariah-based creative economy. The study also suggests enhancing Islamic financial literacy and strengthening digital infrastructure to support the implementation of Islamic economic principles in this sector. Keywords: Creative Economy, Islamic Economic Principles, Digital Technology Abstrak Penelitian ini mengeksplorasi strategi pengembangan ekonomi kreatif di era digital sesuai dengan prinsip ekonomi Islam, seperti keadilan, transparansi, dan larangan terhadap riba dan maysir. Menggunakan metode tinjauan literatur dan analisis teoretis, penelitian ini menganalisis kesesuaian antara praktik ekonomi kreatif dengan nilai-nilai syariah. Sumber data meliputi jurnal, buku, dan publikasi terkait, dengan analisis konten untuk mengidentifikasi strategi yang sesuai dengan ekonomi kreatif berbasis syariah. Hasil menunjukkan bahwa penerapan prinsip ekonomi Islam dapat diwujudkan melalui inovasi berbasis nilai-nilai Islam, model bisnis berbagi hasil, dan teknologi digital untuk transparansi. Implikasi praktisnya adalah rekomendasi bagi pelaku usaha untuk menerapkan prinsip syariah dalam strategi bisnis mereka, serta bagi pembuat kebijakan untuk mendukung regulasi yang memfasilitasi ekonomi kreatif berbasis syariah. Penelitian ini juga merekomendasikan peningkatan literasi keuangan syariah dan penguatan infrastruktur digital untuk mendukung penerapan prinsip ekonomi Islam di sektor ini. Kata Kunci: Ekonomi Kreatif, Prinsip Ekonomi Islam, Teknologi Digital